2013
DOI: 10.1186/1743-422x-10-33
|View full text |Cite
|
Sign up to set email alerts
|

High number of CD56bright NK-cells and persistently low CD4+ T-cells in a hemophiliac HIV/HCV co-infected patient without opportunistic infections

Abstract: BackgroundBoth the human immunodeficiency virus (HIV) and hepatitis C virus (HCV), either alone or as coinfections, persist in their hosts by destroying and/or escaping immune defenses, with high morbidity as consequence. In some cases, however, a balance between infection and immunity is reached, leading to prolonged asymptomatic periods. We report a case of such an indolent co-infection, which could be explained by the development of a peculiar subset of Natural Killer (NK) cells.ResultsPersistently high per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“… 37 An asymptomatic hemophiliac patient co-infected with HIV/HCV also had increased CD56 bri CD16 − NK cells. 38 These results suggest that the CD56 bri CD16 − regulatory NK cells may play a critical role in protecting SARS-CoV-2 infection in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 78%
“… 37 An asymptomatic hemophiliac patient co-infected with HIV/HCV also had increased CD56 bri CD16 − NK cells. 38 These results suggest that the CD56 bri CD16 − regulatory NK cells may play a critical role in protecting SARS-CoV-2 infection in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 78%
“…Virus induced NK cell hyperresponsiveness and cytokine production, particularly in the CD56 bri CD16 -NK subset (Scharenberg et al, 2019). An asymptomatic hemophiliac patient coinfected with HIV/HCV also had increased CD56 bri CD16 -NK cells (Fregni et al, 2013). These results suggested that the CD56 bri CD16regulatory NK cells may play a critical role in the protection of SARS-CoV-2 infection in asymptomatic patients.…”
Section: Cd56 Bri Cd16 -Nk Cells Have Been Linked To Virus Infectionmentioning
confidence: 79%
“…Specific KIR and HLA genotype combinations influence rates of HIV-1 acquisition and disease progression, perhaps due to KIR-mediated NK cell licencing or recognition of HIV-1-derived peptides by non-clonotypic receptors. Interestingly, high percentage of CD56 hi NK cells has been associated with nearly undetectable viral load 50 , suggesting that TCF7 + NKG2C + CD94 + CD56 hi NK cells can control HIV-1. Better understanding of these memory NK cells is hoped to lead to new approaches for preventing and controlling HIV-1 and other infections.…”
Section: Discussionmentioning
confidence: 99%